Analysis of Mobile Based Software Development Model: Systematic Review - Septian Rheno Widianto; Felicia Alhelga S.B.K; Asto Purwanto (Institute of Computer Science (IOCS), 2020)
Software development has various methods, so the choice of software software method for a developer is very important in order to produce quality software according to standards. Based on this description, the importance of knowledge for a developer in choosing a development method, the authors will conduct a literature review in mobile software development methods. The choice of mobile software development method itself is due to the current mass shift among software providers from desktop and web to mobile. This systematic review aims to analyze a mobile-based software development model. In the compilation of this systematic review we use the new PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis). This review shows the predominant method used in the development of mobile-based male devices. The conclusion of this systematic review is that the most commonly used software development models in mobile software.